Decolorization of malachite green by cytochrome c in the mitochondria of the fungus Cunninghamella elegans - Kim, Yong-Hak; Lee, Cheolju; Go, Hayoung; Konishi, Kyoko; Lee, Kangseok; Lau, Peter C. K.; Yu, Myeong-Hee (ELSEVIER SCIENCE INC, 2010)
We studied the decolorization of malachite green (MG) by the fungus Cunninghamella elegans. The mitochondrial activity for MG reduction was increased with a simultaneous increase of a 9-kDa protein, called CeCyt. The presence of cytochrome c in CeCyt protein was determined by optical absorbance spectroscopy with an extinction coefficient (E(550-535)) of 19.7 +/- 6.3 mM(-1) cm(-1) and reduction potential of + 261 mV. When purified CeCyt was added into the mitochondria, the specific activity of CeCyt reached 440 +/- 122 mu mol min(-1) mg(-1) protein. The inhibition of MG reduction by stigmatellin, but not by antimycin A, indicated a possible linkage of CeCyt activity to the Qo site of the bc1 complex. The RT-PCR results showed tight regulation of the cecyt gene expression by reactive oxygen species. We suggest that CeCyt acts as a protein reductant for MG under oxidative stress in a stationary or secondary growth stage of this fungus. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: LEUCOMALACHITE GREEN; B6C3F(1) MICE; TRIPHENYLMETHANE REDUCTASE; GENTIAN-VIOLET; TOXICITY; RATS; DYES; CARCINOGENICITY; DEHYDROGENASE; RESPIRATION